Quantifying systemic risk in Morocco's banking system using Euler indicators and extreme dependence - Khalil Said; Yassine EL Qalli; Abdellali Fadlallah (Cogent Business & Management, 2023)
This article contributes to the quantification of systemic risk within the Moroccan banking system, focusing on listed banks. We utilize indicators derived from Tail Value at Risk and expectiles risk measures, as introduced by El qalli and Said (2013) (El Qalli & Said, 2023), to measure the marginal risk of each component. Additionally, we analyze extreme dependencies within the system using tail dependence coefficients. Empirical results identify Attijariwafa Bank and Banque Centrale Populaire as the most systemic banks in Morocco, carrying the potential to trigger systemic crises.
Keywords: C02; G01; G21; G28; G32; 650; Copulas; Euler Method; extreme dependence; risk measures; Systemic risk